OVERVIEW OF HIGH SODIUM EATING HABITS BEFORE AND AFTER COVID-19 PANDEMIC IN INDONESIA - Afina Rachma Sulistyaning; Farida Farida (GIZI INDONESIA, 2021)
National and global reports showed a high prevalence of sodium intake above the recommended threshold. The pandemic situation might have altered people's eating habits into a healthier diet to improve the immunity system. A high-sodium diet, which has previously been reported as a substantial contributor to several degenerative diseases, might be considered unhealthy eating habits. This study aimed to analyze whether the Covid-19 pandemic has changed the eating habits of high sodium foods and drinks in college students. This cross-sectional study used a food frequency and perception questionnaire in December 2019 - August 2020, conducted in direct interviews and online questionnaires. Forty-three college students enrolled in the present study as respondents. The number of respondents with above-average high sodium eating habits decreased during the covid-19 pandemic, although not statistically significant (p 0.05). More than 60 percent of respondents admitted no significant changes in packaged foods and drinks intake, even though 79.1 percent of respondents reported healthier food and drinks intake during the Covid-19 pandemic. College students/adolescent needs to restrict their consumption of high sodium foods and drinks, especially during the Covid-19 pandemic to improve the immune system. It is also important to emphasize on the massive and continuous promotion of healthy eating habits among college students. Keywords: Covid-19, eating habits, sodium, pandemic ABSTRAK Data nasional dan global menunjukkan tingginya prevalensi konsumsi sodium diatas batas rekomendasi asupan. Kondisi pandemi Covid-19 dapat mengubah pola konsumsi masyarakat menjadi lebih sehat untuk meningkatkan sistem imun. Diet tinggi natrium dilaporkan sebagai penyebab penting dalam perkembangan berbagai penyakit degeneratif, sehingga dapat dikategorikan sebagai kebiasaan makan yang tidak sehat. Penelitian ini bertujuan untuk menganalisis apakah pandemi Covid-19 telah mengubah kebiasaan makan dan minum tinggi natrium di kalangan mahasiswa. Penelitian ini menggunakan metode cross-sectional dengan kuesioner FFQ dan persepsi makan. Penelitian ini berlangsung pada Desember 2019 – Agustus 2020 yang dilaksanakan secara wawancara langsung dan menggunakan kuesioner online. Responden terdiri dari 43 mahasiswa. Jumlah responden dengan pola konsumsi tinggi natrium menurun selama pandemi Covid-19 meskipun tidak signifikan (p 0.05). Lebih dari 60 persen responden mengakui tidak ada perubahan signifikan terkait konsumsi makanan dan minuman kemasan , meskipun 79.1 persen melaporkan konsumsi makanan dan minuman menjadi lebih sehat selama pandemi. Mahasiswa/remaja perlu mengurangi konsumsi makanan dan minuman tinggi natrium, terutama selama masa pandemi Covid-19 untuk meningkatkan sistem imun. Penting untuk diperhatikan bahwa promosi pola konsumsi makanan sehat di lingkup mahasiswa perlu dilakukan dengan langkah yang masif dan berkelanjutan. Kata kunci: Covid-19, pola makan, natrium, pandemi